Relationship between Oil Prices and Russia Exchange Indices: Analysis of Frequency Causality - Nurkhodzha Akbulaev; Imangulu Muradzada; Ziyadhan Hasanov (International Journal of Energy Economics and Policy, 2023)
One of the important research topics is the potential impact of changes in oil supply and demand on current and future price movements or financial market instruments. Especially in developing countries such as Russia, which is an oil and natural gas exporter, sanctions on oil exports affect the country on a macroscale and businesses on a microscale. In this context, the aim of the aforementioned study is to examine the causality relationship between Brent oil price, which is an important input for the chemistry and transportation sectors, and the Moscow Stock Exchange MOEX Chemicals, MOEX Transport, and MOEX Financials indices using Breitung and Candelon frequency causality analysis. For this purpose, monthly data for the period January 2015–December 2022 were analysed first with traditional Granger causality analysis, Toda and Yamamoto causality analysis, and finally with Breitung and Candelon frequency causality analysis. Traditional Granger causality analysis (Toda and Yamamoto causality analysis) revealed a bidirectional causality relationship between Brent Petrol and the MOEX Chemistry and MOEX Finance Indices. However, there is no causality between Brent Petroleum and MOEX Transport. As a result of the Breitung and Candelon frequency causality analysis, causality has been determined from oil prices to stock prices in the chemical sectors, both in the short term, in the medium term, and in the long term. Only short-term causality has been found between Brent oil prices and stock prices in the financial and transportation sectors.